Elastin-derived peptides potentiate atherosclerosis through the immune Neu1–PI3Kγ pathway. (19th December 2013) - Gayral, Stephanie; Garnotel, Roselyne; Castaing-Berthou, Audrey; Blaise, Sebastien; Fougerat, Anne; Berge, Elodie; Montheil, Aurelie; Malet, Nicole; Wymann, Matthias P.; Maurice, Pascal; Debelle, Laurent; Martiny, Laurent; et al.
Abstract: Aims: Elastin is degraded during vascular ageing and its products, elastin-derived peptides (EP), are present in the human blood circulation. EP binds to the elastin receptor complex (ERC) at the cell surface, composed of elastin-binding protein (EBP), a cathepsin A and a neuraminidase 1. Some in vitro functions have clearly been attributed to this binding, but the in vivo implications for arterial diseases have never been clearly investigated. Methods and results: Here, we demonstrate that chronic doses of EP injected into mouse models of atherosclerosis increase atherosclerotic plaque size formation. Similar effects were observed following an injection of a VGVAPG peptide, suggesting that the ERC mediates these effects. The absence of phosphoinositide 3-kinase γ (PI3Kγ) in bone marrow-derived cells prevented EP-induced atherosclerosis development, demonstrating that PI3Kγ drive EP-induced arterial lesions. Accordingly, in vitro studies showed that PI3Kγ was required for EP-induced monocyte migration and ROS production and that this effect was dependent upon neuraminidase activity. Finally, we showed that degradation of elastic lamellae in LDLR −/− mice fed an atherogenic diet correlated with atherosclerotic plaque formation. At the same time, the absence of the cathepsin A–neuraminidase 1 complex in cells of the haematopoietic lineage abolished atheroma plaque size progression and decreased leucocytes infiltration, clearly demonstrating the role of this complex in atherogenesis and suggesting the involvement of endogenous EP. Conclusion: Altogether, this work identifies EP as an enhancer of atherogenesis and defines the Neuraminidase 1/PI3Kγ signalling pathway as a key mediator of this function in vitro and in vivo .